Removal of Methyl Orange using Nanofibrillated Cellulose (NFC) from Kenaf via Cross-Flow Filtration System - Kamaruzaini, Batrisyia Aina; Abdul Hamid, Nor Hazren; Hairom, Nur Hanis Hayati; Mohamad Zayani Zakwan Mohd Zin (Progress in Engineering Application and Technology, 2025)
The increasing presence of synthetic dyes in textile wastewater poses a significant environmental challenge, requiring sustainable and efficient filtration technologies. This study explores the application of nanofibrillated cellulose (NFC) filter paper derived from Kenaf fibers for the removal of Methylene Orange (MO) dye in a cross-flow filtration system. Response Surface Methodology (RSM) with Central Composite Design (CCD) was applied to optimize key parameters, including pH, dye concentration, and pressure, to maximize dye removal efficiency and normalized flux performance. The optimal conditions at pH 10, 1000 ADMI dye concentration, and 3 bar pressure achieved a maximum dye removal efficiency of 54.74 % and a normalized flux of 0.5436. The fouling analysis confirmed cake layer formation as the dominant mechanism, leading to a gradual decline in flux, which was further validated using FESEM and AFM analyses, revealing significant structural modifications in the NFC filter paper post-filtration. The observed morphological changes, including increased fiber compaction and surface roughness reduction, indicate fouling-induced performance limitations, highlighting the necessity for anti-fouling strategies to maintain long-term filtration efficiency. Despite its promising performance in dye removal, the treated wastewater did not fully meet regulatory discharge limits, suggesting the need for additional treatment processes to enhance water quality compliance. These findings suggest that NFC filter paper is a viable and sustainable filtration material for textile wastewater treatment, with potential for further optimization and large-scale industrial applications, ultimately contributing to eco-friendly wastewater management solutions.